2017
DOI: 10.1080/17445647.2017.1302364
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of magnetic susceptibility of the Pyrenean granites

Abstract: In this paper, we report on a compilation of more than 2200 sites (more than 10,000 individual measurements) where anisotropy of magnetic susceptibility (AMS) was studied in granites from the Variscan Pyrenees. The standardization and homogenization of this information has allowed us to produce three Main Maps that synthesize all the information related with the AMS of the Pyrenean granites. We also describe the problems found during the construction of the database (variable geo-positioning, different publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…(3) the existence of S-shaped lineation patterns in the Posets pluton is similar, in both its layout and orientation (Fig. 2), to sigmoidal lineation patterns that have been linked with dextral transpression in many other synkinematic Pyrenean granites (Bouchez & Gleizes, 1995;Gleizes et al 1998b;Román-Berdiel et al 2004;Porquet et al 2017). It thus seems reasonable to consider the Posets pluton as a syn-to late-kinematic granite emplaced during the dextral transpression triggered at the end of the long-lasting Variscan deformational event (D 2 ).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…(3) the existence of S-shaped lineation patterns in the Posets pluton is similar, in both its layout and orientation (Fig. 2), to sigmoidal lineation patterns that have been linked with dextral transpression in many other synkinematic Pyrenean granites (Bouchez & Gleizes, 1995;Gleizes et al 1998b;Román-Berdiel et al 2004;Porquet et al 2017). It thus seems reasonable to consider the Posets pluton as a syn-to late-kinematic granite emplaced during the dextral transpression triggered at the end of the long-lasting Variscan deformational event (D 2 ).…”
Section: Discussionmentioning
confidence: 77%
“…Structural and anisotropy-of-magnetic-susceptibility (AMS) studies of the granitoids in the Pyrenees (Porquet et al 2017) have demonstrated that their emplacement was coeval with the main Variscan D 2 transpressive event (see Bouchez & Gleizes, 1995;Carreras & Druguet, 2014). Most plutons are of Carboniferous age and their emplacement age extends over 70 Myr from 339-337 Ma (granite stocks situated in the core of the Ordovician Aston and Bossòst domes; Mezger & Gerdes, 2016) to 267 ± 1 Ma (Aya pluton in the Western Pyrenees; Denèle et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…During the Carboniferous and Early Permian, the Pyrenees recorded an intense igneous activity including syn-to post-kinematic plutonism and volcanism (Fig. 1B; e.g., Gleizes et al, 1997Gleizes et al, , 2003Denèle et al, 2011Denèle et al, , 2014Porquet et al, 2017), sometimes interpreted as subduction related (e.g., Pereira et al, 2014).…”
Section: Paleozoic History: Variscan Cyclementioning
confidence: 99%
“…In the Iberian Variscan belt, specifically in the Central Iberian Zone (CIZ), in Spain and Portugal, the magnetic behavior of numerous granites has been analyzed. The Spanish granites are mostly ilmenite-type and have been extensively analyzed by several authors, like Aranguren et al (1996); Olivia-Urcia et al (2012); Porquet et al (2017); Román-Berdiel et al (1995). These authors found K m values between 22µSI and 467µSI.…”
Section: Introductionmentioning
confidence: 97%